Employee operating autoclave control panel at Hercules Hopewell plant - Hercules Incorporated (1957)
Two views of an unidentified employee operating the control panel on an autoclave used to process ethyl cellulose manufactured at the Hercules Powder Company plant in Hopewell, Virginia. Ethyl cellulose manufactured by Hercules was commonly purchased by a variety of public and private industries as a raw material for use in plastics, films, lacquers, and other materials. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Ethylcellulose; Hercules Incorporated; Corporations; Cellulose; Machinery; Autoclaves